Evaluation of Suitability of Power Engineering Equipment Elements for Their Use over Fleet Life - Drobenko, B.D.; Budz, S.F.; Astashkin, V.I. (Science and Innovation, 2024)
An approach to the determination of stress-strain state of boiler’s operating elements has been proposed. The possibility of their further exploitation has been discussed. The state of the boiler drums at Unit 6 of the Dobrotvir power plant and at Unit 5 of the Burshtyn power plant of DTEK ZakhidEnergo, PJSC, with exhausted fleet life has been studied. Recommendations on the improvement of techniques for their repair have been developed; a conclusion on the possible extension of their operational lifetime has been made.